Interaction of coronavirus nucleocapsid protein with the 5′‐ and 3′‐ends of the coronavirus genome is involved in genome circularization and negative‐strand RNA synthesis - Lo, Chen‐Yu; Tsai, Tsung‐Lin; Lin, Chao‐Nan; Lin, Ching‐Hung; Wu, Hung‐Yi (The FEBS journal, 2019)
Synthesis of the negative‐strand ((−)‐strand) counterpart is the first step of coronavirus (CoV) replication; however, the detailed mechanism of the early event and the factors involved remain to be determined. Here, using bovine coronavirus (BCoV)‐defective interfering (DI) RNA, we showed that (a) a poly(A) tail with a length of 15 nucleotides (nt) was sufficient to initiate efficient (−)‐strand RNA synthesis and (b) substitution of the poly(A) tail with poly(U), (C) or (G) only slightly decreased the efficiency of (−)‐strand synthesis. The findings indicate that in addition to the poly(A) tail, other factors acting in trans may also participate in (−)‐strand synthesis. The BCoV nucleocapsid (N) protein, an RNA‐binding protein, was therefore tested as a candidate. Based on dissociation constant (Kd) values, it was found that the binding affinity between N protein, but not poly(A)‐binding protein, and the 3′‐terminal 55 nt plus a poly(A), poly(U), poly(C) or poly(G) tail correlates with the efficiency of (−)‐strand synthesis. Such an association was also evidenced by the binding affinity between the N protein and 5′‐ and 3′‐terminal cis‐acting elements important for (−)‐strand synthesis. Further analysis demonstrated that N protein can act as a bridge to facilitate interaction between the 5′‐ and 3′‐ends of the CoV genome, leading to circularization of the genome. Together, the current study extends our understanding of the mechanism of CoV (−)‐strand RNA synthesis through involvement of N protein and genome circularization and thus may explain why the addition of N protein in trans is required for efficient CoV replication. In the initial stage of coronavirus (CoV) (−)‐strand RNA synthesis, binding of the CoV N protein to the 5′‐ and 3′‐terminal structures of (+)‐strand CoV genome leads to circularization of the genome, serving as a platform to recruit cellular proteins and viral replicase proteins including RNA‐dependent RNA polymerase. This then initiates (−)‐strand RNA synthesis.